Construction and analysis of higher order Galerkin variational integrators - Ober-Blöbaum, Sina; Saake, N. (Advances in Computational Mathematics)

Methods for the Design and Development - Anacker, H.; Dellnitz, M.; Flaßkamp, K.; Grocsbrink, S.; Hartmann, P.; Heinzemann, C.; Horenkamp, C.; Kleinjohann, B.; Korf, S.; Krüger, M.; Müller, W.; Ober-Blöbaum, Sina; et al. (Jürgen Gausemeier, Franz Josef Rammig, and Wilhelm Schäfer, editors, Design Methodology for Intelligent Technical Systems)

Dependability of Self-optimizing Mechatronic Systems - Dangelmeier, W.; Dellnitz, M.; Dorociak, R.; Flaßkamp, K.; Gausemeier, J.; Groesbrink, S.; Hartmann, P.; Heinzemann, C.; Hölscher, C.; Iwanek, P.; Keßler, J.H.; Kleinjohann, B.; et al. (Lecture Notes in Mechanical Engineering)

The paradigm of self-optimization - Dellnitz, M.; Dumitrescu, R.; Flaßkamp, K.; Gausemeier, J.; Hartmann, P.; Iwanek, P.; Korf, S.; Krüger, M.; Ober-Blöbaum, Sina; Porrmann, M.; Priesterjahn, C.; Stahl, K.; et al. (Jürgen Gausemeier, Franz Josef Rammig, and Wilhelm Schäfer, editors, Design Methodology for Intelligent Technical Systems)

Variational Lie group formulation of geometrically exact beam dynamics: Synchronous and asynchronous integration - Leitz, T.; Ober-Blöbaum, Sina; Leyendecker, S. (Zdravko Terze, Multibody Dynamics)

Equivariant spectral asymptotics forh-pseudodifferential operators - Weich, Tobias (Journal of Mathematical Physics)
Keywords: Mathematical Physics; Statistical and Nonlinear Physics

Die Rolle von Batteriespeichern in KMU-Microgrids - Vogt, T.; Böcker, Joachim; Kempen, S. (BWK – Das Energie-Fachmagazin – Springer VDI Verlag, Ausgabe 12-2014)

Design Considerations on Peak Power Clipping Thresholds in Microgrids - Vogt, T.; Fröhleke, N.; Böcker, Joachim; Kempen, S. (6th World Conference on Photovoltaic Energy Conversion (WCPEC))

Exponential ergodicity of killed Lévy processes in a finite interval - Kolb, Martin; Savov, Mladen (Electronic Communications in Probability)
Following Bertoin who considered the ergodicity and exponential decay of Lévy processes in a finite domain, we consider general Lévy processes and their ergodicity and exponential decay in a finite interval. More precisely, given Ta=inf{t>0:Xt∉. Under general conditions, e.g. absolute continuity of the transition semigroup of the unkilled Lévy process, we prove that the killed semigroup is a compact operator. Thus, we prove stronger results in view of the exponential ergodicity and estimates of the speed of convergence. Our results are presented in a Lévy processes setting but are well applicable for Markov processes in a finite interval under information about Lebesgue irreducibility of the killed semigroup and that the killed process is a double Feller process. For example, this scheme is applicable to a work of Pistorius.

The Brownian traveller on manifolds - Kolb, Martin; Krejčiřík, David (Journal of Spectral Theory)
We study the influence of the intrinsic curvature on the large time behaviour of the heat equation in a tubular neighbourhood of an unbounded geodesic in a two-dimensional Riemannian manifold. Since we consider killing boundary conditions, there is always an exponential-type decay for the heat semigroup. We show that this exponential-type decay is slower for positively curved manifolds comparing to the flat case. As the main result, we establish a sharp extra polynomial-type decay for the heat semigroup on negatively curved manifolds comparing to the flat case. The proof employs the existence of Hardy-type inequalities for the Dirichlet Laplacian in the tubular neighbourhoods on negatively curved manifolds and the method of self-similar variables and weighted Sobolev spaces for the heat equation.

mm-Wellen- und Electronic-Photonic System-on-Chip Design - Scheytt, Christoph (Fakultätskolloquium der Fakultät für Elektrotechnik und Informationstechnik)

Architectural Low-Power Design Using Transaction-Based System Simulation - Mischkalla, Fabian; Müller, Wolfgang (Embedded Computer Systems: Architectures, Modeling, and Simulation (SAMOS XIV))

Source code annotated memory leak detection for soft real time embedded systems with resource constraints - Joy, M. tech. Mabel Mary; Müller, Wolfgang; Rammig, Franz-Josef (12th IEEE International conference on Embedded Computing)

Advanced SoC Virtual Prototyping for System-Level Power Planning and Validation - Mischkalla, Fabian; Müller, Wolfgang (PATMOS 2014)

Fault Effect Modeling in a Heterogeneous SystemC Based Virtual Platform Framework for Cyber Physical Systems - Becker, Markus; Kuznik, Christoph; Müller, Wolfgang
This paper presents an advanced eight levels spanning SystemC based virtual platform methodology and framework - referred to as HeroeS 3 - providing smooth application to platform mapping and continuous co-refinement of a virtual prototype with its physical environment model. For heterogeneity support, various SystemC extensions are combined covering continuous/discrete models of computation and different communication abstractions, such as analog mixed-signal models, abstract RTOS/HAL/middleware models, TLM bus models, and QEMU wrappers. We enable dependability assessment by Fault Effect Modeling (FEM) at the virtual prototype in order to avoid risking physical injury or damage. Also, simulation results are deterministic and can be evaluated interactively or offline. We apply FEM to both the physical environment model and the different abstractions of the virtual prototype. Currently, we focus on sensor failures and application control flow errors.
Keywords: Computational modeling; Finite element analysis; Prototypes; Abstracts; Software; Fault tolerance; Fault tolerant systems

An Assisted Single Source Verification Metric Model Code Generation Methodology - Kuznik, Christoph; Müller, Wolfgang; Defo, Gilles Bertrand
The ever-increasing complexity of heterogeneous electronic systems demand for intensified abstraction and automation efforts to improve design, verification and validation productivity, especially in earlier phases of system engineering. Within the verification activity various metrics can be applied to determine functional correctness or the overall progress. Here, a supporting verification methodology defining high-level verification planning down to the actual metric code development is essential. Moreover, an advanced assistance for the designer, such as a tooling infrastructure to automatize and accelerate the metric code implementation, is needed to minimize the influence of errorprone manual coding. In this article we present a single-source verification metric code-generation methodology for improved coverage automation. We determine (i) a suitable metric model for model-based capture of verification metrics as well as (ii) an assisted model-based processing and generation flow of the verification environment and metric skeletons. We apply our method to a SystemC case-study, in doing so, targeting metric code implementation productivity and consistency enhancement.
Keywords: System Design; Verification

Modellierung effizienter Stresstest-Umgebungen für virtuelle Prototypen mit SVM - Kuznik, Christoph; Müller, Wolfgang (26. ITG / GI / GMM Workshop Testmethoden und Zuverlässigkeit von Schaltungen und Systemen)
Zur Sicherstellung hoher Zuverlässigkeits- und Fehlertoleranzwerte von Schaltungen und ganzen Systemen finden vermehrt Test- und Verifikationsmethoden Anwendung die einen virtuellen Prototypen (VP) des Systems bereits frühzeitig im Entwurfsablauf einem Stresstest unterziehen. Hierbei werden speziell für die Domäne relevante Fehlerinjektoren verwendet (Digital, Mixed-Signal, Mechanik) die anhand von Fehlermodellen geeignete Testfälle erzeugen und in das System über Stimuli bzw. direkt injizieren. Jede effektive Anwendung einer Methode bedingt jedoch auch das Vorhandensein einer zugrundeliegenden Methodik. In diesem Beitrag wird die System Verification Methodology (SVM) vorgestellt werden, eine universell einsetzbare und erweiterbare Infrastruktur zur Beschreibung von Testumgebungen auf Basis der SystemC Sprache und Simulationskernels.

Semi-automatische Generierung von Überdeckungsmetriken mittels methodischer Verikationsplan Verarbeitung - Kuznik, Christoph; Defo, Bertrand Gilles; Müller, Wolfgang (17. Workshop Methoden und Beschreibungssprachen zur Modellierung und Verifikation von Schaltungen und Systemen (MBMV 2014))

An Assisted Single Source Verification Metric Model Code Generation Methodology - Kuznik, Christoph; Defo, Bertrand Gilles; Müller, Wolfgang (Electronic System Level Synthesis Conference (ESLSyn))

Lecture meets laboratory experimental experiences for large audiences: Concept and implementation - Temmen, Katrin; Nofen, Barbara; Wehebrink, Markus (2014 IEEE Global Engineering Education Conference (EDUCON))

Resonance chains in open systems, generalized zeta functions and clustering of the length spectrum - Barkhofen, Sonja; Faure, F; Weich, Tobias (Nonlinearity)
Keywords: Applied Mathematics; General Physics and Astronomy; Mathematical Physics; Statistical and Nonlinear Physics

Formation and interaction of resonance chains in the open three-disk system - Weich, Tobias; Barkhofen, Sonja; Kuhl, U; Poli, C; Schomerus, H (New Journal of Physics)
Keywords: General Physics and Astronomy

PU-CMA-QAM BASED MIMO EQUALIZATION IN DSP-ENABLED PDM-16-QAM RECEIVERS - Panhwar, M. F.; Sandel, D.; Woerdehoff, C.; Puntsri, K.; Hussin, S.; Noé, Reinhold (2014 OPTOELECTRONICS AND COMMUNICATIONS CONFERENCE AND AUSTRALIAN CONFERENCE ON OPTICAL FIBRE TECHNOLOGY (OECC/ACOFT 2014))

Fiber nonlinearity Mitigation in CO-OFDM Systems using Dual Compensators - Hussin, S.; Noé, Reinhold (2014 IEEE PHOTONICS CONFERENCE (IPC))

REALTIME DIGITAL SIGNAL PROCESSING IN COHERENT OPTICAL PDM-QPSK AND PDM-16-QAM TRANSMISSION - Noé, Reinhold; Panhwar, M. F.; Woerdehoff, C.; Sandel, D. (2014 PROCEEDINGS OF THE 22ND EUROPEAN SIGNAL PROCESSING CONFERENCE (EUSIPCO))

SIMPLE POLARIZATION-DEPENDENT LOSS MEASUREMENT BASED ON POLARIZATION SCRAMBLING - Koch, B.; Noé, Reinhold; Mirvoda, V.; Sandel, D.; Panhwar, M. F. (2014 OPTOELECTRONICS AND COMMUNICATIONS CONFERENCE AND AUSTRALIAN CONFERENCE ON OPTICAL FIBRE TECHNOLOGY (OECC/ACOFT 2014))

Versatile endless optical polarization controller/tracker/demultiplexer - Koch, Benjamin; Noé, Reinhold; Sandel, David; Mirvoda, Vitali (OPTICS EXPRESS)

IMPROVEMENT OF RF-PILOT PHASE NOISE COMPENSATION FOR CO-OFDM TRANSMISSION SYSTEMS VIA COMMON PHASE ERROR EQUALIZER - Hussin, S.; Noé, Reinhold; Panhwar, M. F. (2014 OPTOELECTRONICS AND COMMUNICATIONS CONFERENCE AND AUSTRALIAN CONFERENCE ON OPTICAL FIBRE TECHNOLOGY (OECC/ACOFT 2014))

40 dB CROSSTALK SUPPRESSION IN HIGH-PRECISION ENDLESS POLARIZATION CONTROL - Koch, B.; Noé, Reinhold; Mirvoda, V.; Sandel, D.; Panhwar, M. F. (2014 OPTOELECTRONICS AND COMMUNICATIONS CONFERENCE AND AUSTRALIAN CONFERENCE ON OPTICAL FIBRE TECHNOLOGY (OECC/ACOFT 2014))

APD-BASED INTERFERENCE DETECTORS YIELD 7-dB DYNAMIC RANGE OF 70-krad/s PDM-DPSK ENDLESS POLARIZATION DEMULTIPLEXER - Koch, B.; Noé, Reinhold; Mirvoda, V.; Sandel, D.; Panhwar, M. F. (2014 OPTOELECTRONICS AND COMMUNICATIONS CONFERENCE AND AUSTRALIAN CONFERENCE ON OPTICAL FIBRE TECHNOLOGY (OECC/ACOFT 2014))

1-THz Bandwidth of 70-krad/s Endless Optical Polarization Control - Koch, Benjamin; Noé, Reinhold; Mirvoda, Vitali; Sandel, David (2014 OPTICAL FIBER COMMUNICATIONS CONFERENCE AND EXHIBITION (OFC))

APD-BASED INTERFERENCE DETECTORS YIELD 7-dB DYNAMIC RANGE OF 70-krad/s PDM-DPSK ENDLESS POLARIZATION DEMULTIPLEXER - Koch, B.; Noé, Reinhold; Mirvoda, V.; Sandel, D.; Panhwar, M. F. (2014 OPTOELECTRONICS AND COMMUNICATIONS CONFERENCE AND AUSTRALIAN CONFERENCE ON OPTICAL FIBRE TECHNOLOGY (OECC/ACOFT 2014))

40 dB CROSSTALK SUPPRESSION IN HIGH-PRECISION ENDLESS POLARIZATION CONTROL - Koch, B.; Noé, Reinhold; Mirvoda, V.; Sandel, D.; Panhwar, M. F. (2014 OPTOELECTRONICS AND COMMUNICATIONS CONFERENCE AND AUSTRALIAN CONFERENCE ON OPTICAL FIBRE TECHNOLOGY (OECC/ACOFT 2014))

1-THz bandwidth of 70-krad/s endless optical polarization control - Koch, Benjamin; Noé, Reinhold; Mirvoda, Vitali; Sandel, David (OFC 2014)

Convolution algebras for Heckman–Opdam polynomials derived from compact Grassmannians - Rösler, Margit; Remling, Heiko (Journal of Approximation Theory)
Keywords: Applied Mathematics; General Mathematics; Numerical Analysis; Analysis

Design and Measurement Techniques for an 80 Gb/s 1-Tap Decision Feedback Equalizer - Awny, Ahmed; Möller, Lothar; Junio, Josef; Scheytt, Christoph; Thiede, Andreas (IEEE JOURNAL OF SOLID-STATE CIRCUITS)
A millimeter wave frequency mixed-signal design of a 1-tap half-rate look-ahead decision feedback equalizer for 80 Gb/s short-reach optical communication systems is presented. On-wafer tests are developed to determine the maximum operating bit rate of the equalizer. Results are also presented for intersymbol interference mitigation at 80 Gb/s for a 20 GHz bandwidth-limited channel. Further improvements on the architecture of the 80 Gb/s equalizer are discussed and used in the design and on-wafer measurement of a 110 Gb/s equalizer. The equalizers are designed in a 0.13 μm SiGe:C BiCMOS technology. The 80 and 110 Gb/s versions dissipate 4 and 5.75 W, respectively and occupy 2 and 2.56 mm 2 , respectively.

FIBER NONLINEARITY TOLERANCE OF PARTIAL PILOT FILLING IN CO-OFDM TRANSMISSION SYSTEMS - Hussin, S.; Noé, Reinhold; Panhwar, M. F. (2014 OPTOELECTRONICS AND COMMUNICATIONS CONFERENCE AND AUSTRALIAN CONFERENCE ON OPTICAL FIBRE TECHNOLOGY (OECC/ACOFT 2014))

1-THz Bandwidth of 70-krad/s Endless Optical Polarization Control - Koch, Benjamin; Noé, Reinhold; Mirvoda, Vitali; Sandel, David (2014 OPTICAL FIBER COMMUNICATIONS CONFERENCE AND EXHIBITION (OFC))

Optimizing spatial filters for the extraction of envelope-coupled neural oscillations - Dähne, S.; Nikulin, V. V.; Ramírez, D.; Schreier, P. J.; Müller, K.-R.; Haufe, S. (Proc. Int. Work. Pattern Recognition In Neuroimaging)
Amplitude-to-amplitude interactions between neural oscillations are of a special interest as they show how the strength of spatial synchronization in different neuronal populations relates to each other during a given task. While, previously, amplitude-to-amplitude correlations were studied primarily on the sensor level, we present a source separation approach using spatial filters which maximize the correlation between the envelopes of brain oscillations recorded with electro-/magnetencephalography (EEG/MEG) or intracranial multichannel recordings. Our approach, which is called canonical source power correlation analysis (cSPoC), is thereby capable of extracting genuine brain oscillations solely based on their assumed coupling behavior even when the signal-to-noise ratio of the signals is low.

Testing blind separability of complex Gaussian mixtures - Ramírez, D.; Schreier, P. J.; Vía, J.; Santamaría, I. (Signal Process.)
The separation of a complex mixture based solely on second-order statistics can be achieved using the Strong Uncorrelating Transform (SUT) if and only if all sources have distinct circularity coefficients. However, in most problems we do not know the circularity coefficients, and they must be estimated from observed data. In this work, we propose a detector, based on the generalized likelihood ratio test (GLRT), to test the separability of a complex Gaussian mixture using the SUT. For the separable case (distinct circularity coefficients), the maximum likelihood (ML) estimates are straightforward. On the other hand, for the non-separable case (at least one circularity coefficient has multiplicity greater than one), the ML estimates are much more difficult to obtain. To set the threshold, we exploit Wilks’ theorem, which gives the asymptotic distribution of the GLRT under the null hypothesis. Finally, numerical simulations show the good performance of the proposed detector and the accuracy of Wilks’ approximation.

A Bayesian approach for adaptive multiantenna sensing in cognitive radio networks - Manco-Vásquez, J.; Lázaro-Gredilla, M.; Ramírez, D.; Vía, J.; Santamaría, I. (Signal Process.)

Optimum analog receive filters for detection and inference under a sampling rate constraint - Stein, Manuel; Lenz, Andreas; Mezghani, Amine; Nossek, Josef A. (Proc.\ IEEE Int.\ Conf.\ Acoustics, Speech and Signal Process.)

Spatial Shaping and Precoding Design for Underlay MIMO Interference Channels - Lameiro, Christian; Utschick, Wolfgang; Santamaría, Ignacio (Proc. Int. ITG Work. Smart Antennas)

Information-preserving spatial filtering for direction-of-arrival estimation - Stein, Manuel; Castañeda, Mario; Nossek, Josef A. (Proc.\ ITG Int.\ Work. Smart Ant.)

Neue Anwendungsgebiete für Computer Assisted Surgery (CAS) - Schreier, Peter J. (ForschungsForum Paderborn)

Will the 1-bit GNSS receiver prevail? - Stein, Manuel; Nossek, Josef A. (Proc. of IEEE/ION PLANS 2014)

An asymptotic GLRT for the detection of cyclostationary signals - Ramírez, D.; Scharf, L. L.; Vía, J.; Santamaría, I.; Schreier, P. J. (Proc.\ IEEE Int.\ Conf.\ Acoustics, Speech and Signal Process.)
We derive the generalized likelihood ratio test (GLRT) for detecting cyclostationarity in scalar-valued time series. The main idea behind our approach is Gladyshev’s relationship, which states that when the scalar-valued cyclostationary sig- nal is blocked at the known cycle period it produces a vector- valued wide-sense stationary process. This result amounts to saying that the covariance matrix of the vector obtained by stacking all observations of the time series is block-Toeplitz if the signal is cyclostationary, and Toeplitz if the signal is wide- sense stationary. The derivation of the GLRT requires the maximum likelihood estimates of Toeplitz and block-Toeplitz matrices. This can be managed asymptotically (for large num- berofsamples)exploitingSzego ̈’stheoremanditsgeneraliza- tion for vector-valued processes. Simulation results show the good performance of the proposed GLRT.

Regularized successive interference cancellation (SIC) under mismatched modeling - Tong, Jun; Guo, Qinghua; Schreier, Peter J.; Xi, Jiangtao (Proc.\ IEEE Work.\ Stat.\ Signal Process.)
Successive interference cancellation (SIC) has been extensively applied to estimate transmit signals in communication systems. When the channel state information (CSI) and noise statistics are imperfectly estimated, the standard SIC estimators that ignore the model mismatch may perform poorly. This paper introduces regularized SIC estimation to provide robustness against the model mismatch. Suboptimal, low-complexity implementations using (sorted) QR decomposition and approximate choice of regularization parameters are also introduced. Simulation examples demonstrate that the regularized SIC estimators can significantly outperform the standard version.

Information-preserving transformations for signal parameter estimation - Stein, Manuel; Castañeda, Mario; Mezghani, Amine; Nossek, Josef A. (IEEE Signal Process.\ Lett.)

Fast and Open Virtual Platforms for TriCore-based SoCs Using QEMU - Koppelmann, Bastian; Messidat, Bernd; Becker, Markus; Müller, Wolfgang; Scheytt, J. Christoph (Proceedings of the Design and Verification Conference Europe (DVCON Europe))
In this paper, we present an efficient approach to virtual platform modeling for TriCore-based SoCs by combining fast and open software emulation with IEEE-1666 Standard SystemC simulation. For evaluation we consider Infineon's recently introduced AURIX processor family as a target platform, which utilizes multiple CPU cores operating in lockstep mode, memories, hierarchical buses, and a rich set of peripherals. For SoC prototyping, we integrate the fast and open instruction accurate QEMU software emulator with the TLMu library for SystemC co-verification. This article reports our most recent efforts of the implementation of the TriCore instruction set for QEMU. The experimental results demonstrate the functional correctness and performance of our TriCore implementation.
Keywords: System Design; Verification

On Hardy spaces of local and nonlocal operators - Bogdan, Krzysztof; Dyda, Bartłomiej; Luks, Tomasz (Hiroshima Mathematical Journal)

Multi-antenna spectrum sensing by exploiting spatio-temporal correlation - Ali, S.; Ramírez, D.; Jansson, M.; Seco-Granados, G.; López-Salcedo, J. A. (Eurasip\ J.\ Applied Signal Process.)
In this paper, we propose a novel mechanism for spectrum sensing that leads us to exploit the spatio-temporal correlation present in the received signal at a multi-antenna receiver. For the proposed mechanism, we formulate the spectrum sensing scheme by adopting the generalized likelihood ratio test (GLRT). However, the GLRT degenerates in the case of limited sample support. To circumvent this problem, several extensions are proposed that bring robustness to the GLRT in the case of high dimensionality and small sample size. In order to achieve these sample-efficient detection schemes, we modify the GLRT-based detector by exploiting the covariance structure and factoring the large spatio-temporal covariance matrix into spatial and temporal covariance matrices. The performance of the proposed detectors is evaluated by means of numerical simulations, showing important advantages over existing detectors.

A flag representation for finite collections of subspaces of mixed dimensions - Draper, Bruce; Kirby, Michael; Marks, Justin; Marrinan, Tim; Peterson, Chris (Lin.\ Alg.\ Appl.)

Input-to-State Stability for Discrete-Time Monotone Systems - Rüffer, Björn S.; Sailer, Rudolf (Proc. 21st Int. Symp. Mathematical Theory of Networks and Systems (MTNS))
It is well known that input-to-state stability admits an astonishing number of equivalent characterizations. Here it is shown that for monotone systems on $\Rnp$ there are some additional characterizations that are useful for network stability analysis. These characterizations include system theoretic properties, algebraic properties, as well as the problem of finding simultaneous bounds on solutions to a collection of inequalities.

Accurate Performance Analysis of Hadamard Ratio Test for Robust Spectrum Sensing - Huang, L.; Xiao, Y-.H.; So, H. C.; Fang, J. (IEEE Transactions on Wireless Communications)

Finding the Subspace Mean or Median to Fit Your Need - Marrinan, Tim; Draper, Bruce; Beveridge, J. Ross; Kirby, Michael; Peterson, Chris (CVPR)

Finding brain oscillations with power dependencies in neuroimaging data - Dähne, S.; Nikulin, V. V.; Ramírez, D.; Schreier, P. J.; Müller, K.-R.; Haufe, S. (NeuroImage)
Phase synchronization among neuronal oscillations within the same frequency band has been hypothesized to be a major mechanism for communication between different brain areas. On the other hand, cross-frequency com- munications are more flexible allowing interactions between oscillations with different frequencies. Among such cross-frequency interactions amplitude-to-amplitude interactions are of a special interest as they show how the strength of spatial synchronization in different neuronal populations relates to each other during a given task. While, previously, amplitude-to-amplitude correlations were studied primarily on the sensor level, we present a source separation approach using spatial filters which maximize the correlation between the envelopes of brain oscillations recorded with electro-/magnetoencephalography (EEG/MEG) or intracranial multichannel re- cordings. Our approach, which is called canonical source power correlation analysis (cSPoC), is thereby capable of extracting genuine brain oscillations solely based on their assumed coupling behavior even when the signal-to- noise ratio of the signals is low. In addition to using cSPoC for the analysis of cross-frequency interactions in the same subject, we show that it can also be utilized for studying amplitude dynamics of neuronal oscillations across subjects. We assess the performance of cSPoC in simulations as well as in three distinctively different analysis sce- narios of real EEG data, each involving several subjects. In the simulations, cSPoC outperforms unsupervised state-of-the-art approaches. In the analysis of real EEG recordings, we demonstrate excellent unsupervised dis- covery of meaningful power-to-power couplings, within as well as across subjects and frequency bands.

Detecting Directionality in Random Fields Using the Monogenic Signal - Olhede, S. C.; Ramírez, D.; Schreier, P. J. (IEEE Trans.\ Inform.\ Theory)
Detecting and analyzing directional structures in images is important in many applications since one-dimensional patterns often correspond to important features such as object contours or trajectories. Classifying a structure as directional or non-directional requires a measure to quantify the degree of directionality and a threshold, which needs to be chosen based on the statistics of the image. In order to do this, we model the image as a random field. So far, little research has been performed on analyzing directionality in random fields. In this paper, we propose a measure to quantify the degree of directionality based on the random monogenic signal, which enables a unique decomposition of a 2D signal into local amplitude, local orientation, and local phase. We investigate the second-order statistical properties of the monogenic signal for isotropic, anisotropic, and unidirectional random fields. We analyze our measure of directionality for finite-size sample images, and determine a threshold to distinguish between unidirectional and non-unidirectional random fields, which allows the automatic classification of images.

A Quadratically Convergent Method for Interference Alignment in MIMO Interference Channels - Lameiro, Christian; Santamaría, Ignacio (IEEE Signal Process. Lett.)
Alternating minimization and steepest descent are commonly used strategies to obtain interference alignment (IA) solutions in the $K$-user multiple-input multiple-output (MIMO) interference channel (IC). Although these algorithms are shown to converge monotonically, they experience a poor convergence rate, requiring an enormous amount of iterations which substantially increases with the size of the scenario. To alleviate this drawback, in this letter we resort to the Gauss-Newton (GN) method, which is well-known to experience quadratic convergence when the iterates are sufficiently close to the optimum. We discuss the convergence properties of the proposed GN algorithm and provide several numerical examples showing that it always converges to the optimum with quadratic rate, reducing dramatically the required computation time in comparison to other algorithms, hence paving a new way for the design of IA algorithms.

Interference-Temperature Limit for Cognitive Radio Networks with MIMO Primary Users - Lameiro, Christian; Utschick, Wolfgang; Santamaría, Ignacio (Proc.\ Asilomar Conf.\ Signals Syst.\ Computers)
This paper derives the interference-temperature (IT) limit for a multi-antenna primary user (PU) with a rate constraint. While in the case of a single-antenna PU there is a one-to-one mapping between IT and achievable rate, this correspondence does not hold anymore when a multiple-input multiple-output (MIMO) system is considered. In such cases, the spatial distribution of the interference must be taken into account, since it strongly affects the PU performance. To this end, we derive a closed-form expression for the maximum IT that can be tolerated by identifying the worst-case interference covariance matrix, which results in a multilevel waterfilling problem.

A Regularized Maximum Likelihood Estimator for the Period of a Cyclostationary Process - Ramírez, D.; Schreier, P. J.; Vía, J.; Santamaría, I.; Scharf, L. L. (Proc.\ Asilomar Conf.\ Signals Syst.\ Computers)
We derive an estimator of the cycle period of a univariate cyclostationary process based on an information- theoretic criterion. Transforming the univariate cyclostationary process into a vector-valued wide-sense stationary process allows us to obtain the structure of the covariance matrix, which is block-Toeplitz, and its block size depends on the unknown cycle period. Therefore, we sweep the block size and obtain the ML estimate of the covariance matrix, required for the information- theoretic criterion. Since there are no closed-form ML estimates of block-Toeplitz matrices, we asymptotically approximate them as block-circulant. Finally, some numerical examples show the good performance of the proposed estimator.

Optimization and estimation of complex-valued signals - Adali, Tulay; Schreier, Peter J. (IEEE Signal Processing Magazine)
Complex-valued signals occur in many areas of science and engineering and are thus of fundamental interest. When developing signal processing methods in the complex domain, there are two key issues: making use of the full statistical information and optimization. In this article, we review the necessary tools to address these two key issues and provide examples in filtering and blind source separation (BSS) that utilize these tools.

Interference Shaping Constraints for Underlay MIMO Interference Channels - Lameiro, Christian; Santamaría, Ignacio; Utschick, Wolfgang (Proc.\ IEEE Int.\ Conf.\ Acoustics, Speech and Signal Process.)

A lower bound for the Fisher information measure - Stein, Manuel; Mezghani, Amine; Nossek, Josef A. (IEEE Signal Process.\ Lett.)

Hardness of approximation for quantum problems - Gharibian, Sevag; Kempe, Julia (Quantum Information & Computation)
The polynomial hierarchy plays a central role in classical complexity theory. Here, we define a quantum generalization of the polynomial hierarchy, and initiate its study. We show that not only are there natural complete problems for the second level of this quantum hierarchy, but that these problems are in fact hard to approximate. Using the same techniques, we also obtain hardness of approximation for the class QCMA. Our approach is based on the use of dispersers, and is inspired by the classical results of Umans regarding hardness of approximation for the second level of the classical polynomial hierarchy [Umans, FOCS 1999]. The problems for which we prove hardness of approximation for include, among others, a quantum version of the Succinct Set Cover problem, and a variant of the local Hamiltonian problem with hybrid classical-quantum ground states.
Keywords: Hardness of approximation; polynomial time hierarchy; succinct set cover; quantum complexity

Gate-efficient discrete simulations of continuous-time quantum query algorithms - W. Berry, Dominic; Cleve, Richard; Gharibian, Sevag (Quantum Information & Computation)
We show how to efficiently simulate continuous-time quantum query algorithms that run in time T in a manner that preserves the query complexity (within a polylogarithmic factor) while also incurring a small overhead cost in the total number of gates between queries. By small overhead, we mean T within a factor that is polylogarithmic in terms of T and a cost measure that reflects the cost of computing the driving Hamiltonian. This permits any continuous-time quantum algorithm based on an efficiently computable driving Hamiltonian to be converted into a gate-efficient algorithm with similar running time.

Computation of Galois groups of rational polynomials - Fieker, Claus; Klüners, Jürgen (LMS Journal of Computation and Mathematics)
Computational Galois theory, in particular the problem of computing the Galois group of a given polynomial, is a very old problem. Currently, the best algorithmic solution is Stauduhar’s method. Computationally, one of the key challenges in the application of Stauduhar’s method is to find, for a given pair of groups H<G, a G-relative H-invariant, that is a multivariate polynomial F that is H-invariant, but not G-invariant. While generic, theoretical methods are known to find such F, in general they yield impractical answers. We give a general method for computing invariants of large degree which improves on previous known methods, as well as various special invariants that are derived from the structure of the groups. We then apply our new invariants to the task of computing the Galois groups of polynomials over the rational numbers, resulting in the first practical degree independent algorithm.
Keywords: Computational Theory and Mathematics; General Mathematics

Low temperature fabrication of a ZnO nanoparticle thin-film transistor suitable for flexible electronics - Vidor, F.F.; Wirth, G.I.; Hilleringmann, Ulrich (Microelectronics Reliability)
Keywords: Electrical and Electronic Engineering; Surfaces; Coatings and Films; Safety; Risk; Reliability and Quality; Condensed Matter Physics; Atomic and Molecular Physics; and Optics; Electronic; Optical and Magnetic Materials

Stability Analysis of a Charge Pump Phase-Locked Loop Using Autonomous Difference Equations - Hangmann, Christian; Hedayat, Christian; Hilleringmann, Ulrich (IEEE Transactions on Circuits and Systems I: Regular Papers)
Keywords: Electrical and Electronic Engineering

One-class genera of maximal integral quadratic forms - Kirschmer, Markus (Journal of Number Theory)
Suppose Q is a definite quadratic form on a vector space V over some totally real field K ≠ Q. Then the maximal integral Zₖ-lattices in (V,Q) are locally isometric everywhere and hence form a single genus. We enumerate all orthogonal spaces (V,Q) of dimension at least 3, where the corresponding genus of maximal integral lattices consists of a single isometry class. It turns out, there are 471 such genera. Moreover, the dimension of V and the degree of K are bounded by 6 and 5 respectively. This classification also yields all maximal quaternion orders of type number one.
Keywords: Algebra and Number Theory

Anodized Aluminum as Effective and Cheap Alternative Substrate for Thermoelectric Generators - Assion, F.; Geneiß, V.; Schönhoff, M.; Hedayat, C.; Hilleringmann, Ulrich (Proceedings of the 11th European Conference on Thermoelectrics)
The wide usage of thermoelectric generators (TEG) is still blocked by very high product costs. This paper presents anodized aluminum (Al) as an effective and cheap alternative for ceramics like alumina (Al2O3) or aluminum nitride (AlN). Al has a significantly higher thermal conductivity as both named ceramics. In addition, the lower thermal stability of Al is still high enough to work with bismuth telluride based modules, which are most common. To show the advantages of the changed substrate, finite element method (FEM) simulations were performed. These simulations show that by changing the cold side substrate material the temperature drop across the substrate is reduced by 60 K. This correlates to a theoretical power gain of more than 20 {%}. Furthermore, Al can be shaped much easier than a ceramic material. The biggest advantage is obviously the price. Anodized Al is around twenty times cheaper than Al2O3. To demonstrate the easy fabrication of the proposed substrate, samples were prepared only with widely used processes like those used for conventional printed circuit boards.

A Flexible Measurement System for the Characterization of Thermoelectric Materials - Schönhoff, M.; Assion, F.; Hilleringmann, Ulrich (Proceedings of the 11th European Conference on Thermoelectrics)
The figure of merit needs to be determined to rate the quality of thermoelectric materials (TM). Therefore, it is necessary to measure all involved parameters—the Seebeck coefficient (S), the thermal conductivity ($λ$), and the electrical conductivity ($σ$).

Replacing TCO electrodes in dye sensitized solar cells by metal grids - Hilleringmann, Ulrich; Kleine, André (SPIE Proceedings)

Lithografie - Hilleringmann, Ulrich (Silizium-Halbleitertechnologie)

Random telegraph signal in nanoparticulated ZnO thin-film transistors - Vidor, FF; Wirth, GI; Hilleringmann, Ulrich (The 40th International Conference on Micro and Nano Engineering (MNE2014))

Embedded UHF RFID tag design process for rubber transmission belt using 3D model - Kanwar, Kelash; Mager, Thomas; Hilleringmann, Ulrich; Geneiss, Volker; Hedayat, Christian (2014 IEEE RFID Technology and Applications Conference (RFID-TA))

Modeling and characterization of CP-PLL phase noise in presence of dead zone - Hangmann, Christian; Wullner, Ingo; Hedayat, Christian; Hilleringmann, Ulrich (2014 IEEE 12th International New Circuits and Systems Conference (NEWCAS))

Titanium disilicide as hot side metallization layer for thermoelectric generators - Hilleringmann, Ulrich; Schonhoff, M.; Assion, F. (2013 Africon)

Computing with subgroups of the modular group - Kirschmer, Markus; LEEDHAM-GREEN, CHARLES (Glasgow Mathematical Journal)
We exhibit a practical algorithm for solving the constructive membership problem for discrete free subgroups of rank 2 in PSL₂(R) or SL₂(R). This algorithm, together with methods for checking whether a two-generator subgroup of PSL₂(R) or SL₂(R) is discrete and free, have been implemented in Magma for groups defined over real algebraic number fields.
Keywords: General Mathematics

The constructive membership problem for discrete free subgroups of rank 2 of SL₂(R) - Eick, B.; Kirschmer, Markus; Leedham-Green, C. (LMS Journal of Computation and Mathematics)
We exhibit a practical algorithm for solving the constructive membership problem for discrete free subgroups of rank 2 in PSL₂(R) or SL₂(R). This algorithm, together with methods for checking whether a two-generator subgroup of PSL₂(R) or SL₂(R) is discrete and free, have been implemented in Magma for groups defined over real algebraic number fields.
Keywords: Computational Theory and Mathematics; General Mathematics

Engineering plasmonic and dielectric directional nanoantennas - Hildebrandt, Andre; Reichelt, Matthias; Meier, Torsten; Förstner, Jens (Ultrafast Phenomena and Nanophotonics XVIII)
Optical and infrared antennas provide a promising way to couple photons in and out of nanoscale structures. As counterpart to conventional radio antennas, they are able to increase optical felds in sub-wavelength volumes, to enhance excitation and emission of quantum emitters or to direct light, radiated by quantum emitters. The directed emission of these antennas has been mainly pursued by surface plasmon based devices, e.g. Yagi-Uda like antennas, which are rather complicated due to the coupling of several metallic particles. Also, like all metallic structures in optical or infrared regime, these devices are very sensitive to fabrication tolerances and are affected by strong losses. It has been shown recently, that such directed emission can be accomplished by dielectric materials as well. In this paper we present an optimization of nanoscopic antennas in the near infrared regime starting from a metallic Yagi-Uda structure. The optimization is done via a particle-swarm algorithm, using full time domain finite integration simulations to obtain the characteristics of the investigated structure, also taking into account substrates. Furthermore we present a dielectric antenna, which performs even better, due to the lack of losses by an appropriate choice of the dielectric material. These antennas are robust concerning fabrication tolerances and can be realized with different materials for both the antenna and the substrate, without using high index materials.
Keywords: tet_topic_opticalantenna

Analytic moduli spaces of simple sheaves on families of integral curves - Burban, Igor; Kreußler, B. (Mathematische Nachrichten)

Beobachten und Dokumentieren. Basis zur chancengerechten Gestaltung des pädagogischen Alltags - Bruns, Julia; Walter-Laager, C.; Pfiffner, M.; Schwarz, J. (Vorsprung für alle! Erhöhung der Chancengerechtigkeit durch Projekte der Frühpädagogik)

Adaptive Förderung in der elementarpädagogischen Praxis. Eine empirische Studie zum di-daktischen Handeln von Erzieherinnen und Erziehern im Bereich Mathematik - Bruns, Julia

Adaptive mathematische Förderung im Elementarbereich - Empirische Ergebnisse zum didaktischen Handeln von Erzieherinnen - Bruns, Julia; Eichen, Lars (Beiträge zum Mathematikunterricht 2014)

A Scalable Formal Debugging Approach with Auto-Correction Capability based on Static Slicing and Dynamic Ranking for RTL Datapath Designs - Alizadeh, Bijan; Behnam, Payman; Sadeghi-Kohan, Somayeh (IEEE Transactions on Computers)
Keywords: Computational Theory and Mathematics; Hardware and Architecture; Theoretical Computer Science; Software

An off-line MDSI interconnect BIST incorporated in BS 1149.1 - Mohammadi, Marzieh; Sadeghi-Kohan, Somayeh; Masoumi, Nasser; Navabi, Zainalabedin (2014 19th IEEE European Test Symposium (ETS))

Improving polynomial datapath debugging with HEDs - Sadeghi-Kohan, Somayeh; Behnam, Payman; Alizadeh, Bijan; Fujita, Masahiro; Navabi, Zainalabedin (2014 19th IEEE European Test Symposium (ETS))

Verschiebungen an der Grenze zwischen Hardware und Software - Platzner, Marco; Plessl, Christian (Logiken strukturbildender Prozesse: Automatismen)
Im Bereich der Computersysteme ist die Festlegung der Grenze zwischen Hardware und Software eine zentrale Problemstellung. Diese Grenze hat in den letzten Jahrzehnten nicht nur die Entwicklung von Computersystemen bestimmt, sondern auch die Strukturierung der Ausbildung in den Computerwissenschaften beeinﬂusst und sogar zur Entstehung von neuen Forschungsrichtungen geführt. In diesem Beitrag beschäftigen wir uns mit Verschiebungen an der Grenze zwischen Hardware und Software und diskutieren insgesamt drei qualitativ unterschiedliche Formen solcher Verschiebungen. Wir beginnen mit der Entwicklung von Computersystemen im letzten Jahrhundert und der Entstehung dieser Grenze, die Hardware und Software erst als eigenständige Produkte diﬀerenziert. Dann widmen wir uns der Frage, welche Funktionen in einem Computersystem besser in Hardware und welche besser in Software realisiert werden sollten, eine Fragestellung die zu Beginn der 90er-Jahre zur Bildung einer eigenen Forschungsrichtung, dem sogenannten Hardware/Software Co-design, geführt hat. Im Hardware/Software Co-design ﬁndet eine Verschiebung von Funktionen an der Grenze zwischen Hardware und Software während der Entwicklung eines Produktes statt, um Produkteigenschaften zu optimieren. Im fertig entwickelten und eingesetzten Produkt hingegen können wir dann eine feste Grenze zwischen Hardware und Software beobachten. Im dritten Teil dieses Beitrags stellen wir mit selbst-adaptiven Systemen eine hochaktuelle Forschungsrichtung vor. In unserem Kontext bedeutet Selbstadaption, dass ein System Verschiebungen von Funktionen an der Grenze zwischen Hardware und Software autonom während der Betriebszeit vornimmt. Solche Systeme beruhen auf rekonﬁgurierbarer Hardware, einer relativ neuen Technologie mit der die Hardware eines Computers während der Laufzeit verändert werden kann. Diese Technologie führt zu einer durchlässigen Grenze zwischen Hardware und Software bzw. löst sie die herkömmliche Vorstellung einer festen Hardware und einer ﬂexiblen Software damit auf.

Partitioning and Vectorizing Binary Applications for a Reconfigurable Vector Computer - Kenter, Tobias; Vaz, Gavin Francis; Plessl, Christian (Proceedings of the International Symposium on Reconfigurable Computing: Architectures, Tools, and Applications (ARC))
In order to leverage the use of reconfigurable architectures in general-purpose computing, quick and automated methods to find suitable accelerator designs are required. We tackle this challenge in both regards. In order to avoid long synthesis times, we target a vector copro- cessor, implemented on the FPGAs of a Convey HC-1. Previous studies showed that existing tools were not able to accelerate a real-world application with low effort. We present a toolflow to automatically identify suitable loops for vectorization, generate a corresponding hardware/software bipartition, and generate coprocessor code. Where applicable, we leverage outer-loop vectorization. We evaluate our tools with a set of characteristic loops, systematically analyzing different dependency and data layout properties.

Seven Recipes for Setting Your FPGA on Fire – A Cookbook on Heat Generators - Agne, Andreas; Hangmann, Hendrik; Happe, Markus; Platzner, Marco; Plessl, Christian (Microprocessors and Microsystems)
Due to the continuously shrinking device structures and increasing densities of FPGAs, thermal aspects have become the new focus for many research projects over the last years. Most researchers rely on temperature simulations to evaluate their novel thermal management techniques. However, these temperature simulations require a high computational effort if a detailed thermal model is used and their accuracies are often unclear. In contrast to simulations, the use of synthetic heat sources allows for experimental evaluation of temperature management methods. In this paper we investigate the creation of significant rises in temperature on modern FPGAs to enable future evaluation of thermal management techniques based on experiments. To that end, we have developed seven different heat-generating cores that use different subsets of FPGA resources. Our experimental results show that, according to external temperature probes connected to the FPGA’s heat sink, we can increase the temperature by an average of 81 !C. This corresponds to an average increase of 156.3 !C as measured by the built-in thermal diodes of our Virtex-5 FPGAs in less than 30 min by only utilizing about 21 percent of the slices.

Reconstructing AES Key Schedules from Decayed Memory with FPGAs - Riebler, Heinrich; Kenter, Tobias; Plessl, Christian; Sorge, Christoph (Proceedings of Field-Programmable Custom Computing Machines (FCCM))
In this paper, we study how AES key schedules can be reconstructed from decayed memory. This operation is a crucial and time consuming operation when trying to break encryption systems with cold-boot attacks. In software, the reconstruction of the AES master key can be performed using a recursive, branch-and-bound tree-search algorithm that exploits redundancies in the key schedule for constraining the search space. In this work, we investigate how this branch-and-bound algorithm can be accelerated with FPGAs. We translated the recursive search procedure to a state machine with an explicit stack for each recursion level and create optimized datapaths to accelerate in particular the processing of the most frequently accessed tree levels. We support two different decay models, of which especially the more realistic non-idealized asymmetric decay model causes very high runtimes in software. Our implementation on a Maxeler dataflow computing system outperforms a software implementation for this model by up to 27x, which makes cold-boot attacks against AES practical even for high error rates.
Keywords: coldboot

Self-awareness as a Model for Designing and Operating Heterogeneous Multicores - Agne, Andreas; Happe, Markus; Lösch, Achim; Plessl, Christian; Platzner, Marco (ACM Transactions on Reconfigurable Technology and Systems (TRETS))
Self-aware computing is a paradigm for structuring and simplifying the design and operation of computing systems that face unprecedented levels of system dynamics and thus require novel forms of adaptivity. The generality of the paradigm makes it applicable to many types of computing systems and, previously, researchers started to introduce concepts of self-awareness to multicore architectures. In our work we build on a recent reference architectural framework as a model for self-aware computing and instantiate it for an FPGA-based heterogeneous multicore running the ReconOS reconfigurable architecture and operating system. After presenting the model for self-aware computing and ReconOS, we demonstrate with a case study how a multicore application built on the principle of self-awareness, autonomously adapts to changes in the workload and system state. Our work shows that the reference architectural framework as a model for self-aware computing can be practically applied and allows us to structure and simplify the design process, which is essential for designing complex future computing systems.

ReconOS - An Operating System Approach for Reconfigurable Computing - Agne, Andreas; Happe, Markus; Keller, Ariane; Lübbers, Enno; Plattner, Bernhard; Platzner, Marco; Plessl, Christian (IEEE Micro)
The ReconOS operating system for reconfigurable computing offers a unified multi-threaded programming model and operating system services for threads executing in software and threads mapped to reconfigurable hardware. The operating system interface allows hardware threads to interact with software threads using well-known mechanisms such as semaphores, mutexes, condition variables, and message queues. By semantically integrating hardware accelerators into a standard operating system environment, ReconOS allows for rapid design space exploration, supports a structured application development process and improves the portability of applications

Runtime Resource Management in Heterogeneous System Architectures: The SAVE Approach - C. Durelli, Gianluca; Pogliani, Marcello; Miele, Antonio; Plessl, Christian; Riebler, Heinrich; Vaz, Gavin Francis; D. Santambrogio, Marco; Bolchini, Cristiana (Proc. Int. Symp. on Parallel and Distributed Processing with Applications (ISPA))

Deferring Accelerator Offloading Decisions to Application Runtime - Vaz, Gavin Francis; Riebler, Heinrich; Kenter, Tobias; Plessl, Christian (Proceedings of the International Conference on ReConFigurable Computing and FPGAs (ReConFig))
Reconfigurable architectures provide an opportunityto accelerate a wide range of applications, frequentlyby exploiting data-parallelism, where the same operations arehomogeneously executed on a (large) set of data. However, whenthe sequential code is executed on a host CPU and only dataparallelloops are executed on an FPGA coprocessor, a sufficientlylarge number of loop iterations (trip counts) is required, such thatthe control- and data-transfer overheads to the coprocessor canbe amortized. However, the trip count of large data-parallel loopsis frequently not known at compile time, but only at runtime justbefore entering a loop. Therefore, we propose to generate codeboth for the CPU and the coprocessor, and to defer the decisionwhere to execute the appropriate code to the runtime of theapplication when the trip count of the loop can be determinedjust at runtime. We demonstrate how an LLVM compiler basedtoolflow can automatically insert appropriate decision blocks intothe application code. Analyzing popular benchmark suites, weshow that this kind of runtime decisions is often applicable. Thepractical feasibility of our approach is demonstrated by a toolflowthat automatically identifies loops suitable for vectorization andgenerates code for the FPGA coprocessor of a Convey HC-1. Thetoolflow adds decisions based on a comparison of the runtimecomputedtrip counts to thresholds for specific loops and alsoincludes support to move just the required data to the coprocessor.We evaluate the integrated toolflow with characteristic loopsexecuted on different input data sizes.

Kernel-Centric Acceleration of High Accuracy Stereo-Matching - Kenter, Tobias; Schmitz, Henning; Plessl, Christian (Proceedings of the International Conference on ReConFigurable Computing and FPGAs (ReConFig))
Stereo-matching algorithms recently received a lot of attention from the FPGA acceleration community. Presented solutions range from simple, very resource efficient systems with modest matching quality for small embedded systems to sophisticated algorithms with several processing steps, implemented on big FPGAs. In order to achieve high throughput, most implementations strongly focus on pipelining and data reuse between different computation steps. This approach leads to high efficiency, but limits the supported computation patterns and due the high integration of the implementation, adaptions to the algorithm are difficult. In this work, we present a stereo-matching implementation, that starts by offloading individual kernels from the CPU to the FPGA. Between subsequent compute steps on the FPGA, data is stored off-chip in on-board memory of the FPGA accelerator card. This enables us to accelerate the AD-census algorithm with cross-based aggregation and scanline optimization for the first time without algorithmic changes and for up to full HD image dimensions. Analyzing throughput and bandwidth requirements, we outline some trade-offs that are involved with this approach, compared to tighter integration of more kernel loops into one design.

SAVE: Towards efficient resource management in heterogeneous system architectures - C. Durelli, Gianluca; Copolla, Marcello; Djafarian, Karim; Koranaros, George; Miele, Antonio; Paolino, Michele; Pell, Oliver; Plessl, Christian; D. Santambrogio, Marco; Bolchini, Cristiana (Proc. Int. Conf. on Reconfigurable Computing: Architectures, Tools and Applications (ARC))

Accelerating Finite Difference Time Domain Simulations with Reconfigurable Dataflow Computers - Giefers, Heiner; Plessl, Christian; Förstner, Jens (ACM SIGARCH Computer Architecture News)
Keywords: funding-maxup; tet_topic_hpc

The project virtual science fair for promoting inquiry learning - Jonas-Ahrend, Gabriela (Initiatives in mathematics and science education with global implications)